STUDI LITERATUR EFEKTIFITAS KOMPRES HANGAT TERHADAP PENURUNAN SUHU PADA DEMAM THYPOID: STUDI LITERATUR EFEKTIFITAS KOMPRES HANGAT TERHADAP PENURUNAN SUHU PADA DEMAM THYPOID - Ningsih, Fira Septia (Universitas Harapan Bangsa Purwokerto, 2020)
AbstractFever is an increase in body temperature above normal. It can also be a sign that the body has an infection. One of them is typhoid fever, which is a fever that is experienced by typhoid sufferers because of an acute infection in the digestive tract. Reducing or controlling fever in a fever can be done in various ways, one of which is the warm compress method. This study is a literature review (literature review) which aims to examine various studies on the relationship of giving warm compresses in reducing fever in patients with typhoid. The search for journal articles was carried out using several databases namely google proquise and google scholar by entering the keywords